Leaving Whiskey Bend - Garlock, Dorothy (New York : Grand Central Pub., 2008)
When their friend is assaulted in the street of their hard-drinking, gun-toting Colorado town, a young schoolteacher and a spinster set out in an open wagon to find a safer life, an endeavor that pits them against violent natural elements and their friends.
Keywords: Vigilantes -- Fiction; Abused women -- Fiction; Western stories